Influence of the cell geometry on the conversion efficiency of oxidation catalysts under real driving conditions. (1st April 2021) - Piqueras, Pedro; Ruiz, María José; Herreros, José Martín; Tsolakis, Athanasios
Graphical abstract: Highlights: Understanding of cell and washcoat geometry on catalyst conversion efficiency. Square and triangular cells are evaluated under dynamic driving conditions. Positive effect of high gas and low washcoat specific surfaces on conversion. Best conversion efficiency is found for triangular cells and ceramic substrates. Cell geometry optimization is not enough to offset CO emission spikes penalties. Abstract: Worldwide pollutant regulations applied to the transportation sector are progressively tightening the emission limits and widening the operating conditions of the type approval tests. As a result, the layout and thermal management of the exhaust system is becoming highly complex looking to achieve early catalytic converter activation. On this regard, the monolith meso-geometry plays a primary role to optimise the pollutants conversion efficiency. The geometrical characteristics simultaneously affect and trade-off multiple flow phenomena as the exhaust gas is transported through the channels. These include the bulk gas and internal pore diffusion towards the active sites in addition to the heat transfer including convection, radial conductivity and thermal capacitance. In this work, the impacts of the cell size, cross-section shape, washcoat loading and substrate material on CO and HC conversion efficiency have been investigated under representative real driving conditions. From the real driving conditions experimental data, the study decouples the influence of the washcoat loading from the cell size and material applying a catalytic converter model. Detailed expressions are provided for the calculation of the specific surfaces and heat and mass transfer parameters as a function of the cell and washcoat meso-geometry in square and triangular cells. Therefore, this work enables to identify the processes which govern the catalytic abatement of pollutant emissions. In particular, the role of the gas and washcoat specific surfaces is highlighted because of its importance on the optimization of the mass transfer process by means of a proper cell geometry selection. In parallel, the differences in the change of the CO and HC abatement patterns, which are explained by the characteristic CO emission spikes in accelerations and the HC accumulation, contribute to evidence the limitations on the conversion efficiency benefit that the optimum cell geometry and washcoat loading can provide.